Tinjauan Yuridis Sanksi Pidana Delik Perbuatan Cabul terhadap Anak dalam Undang-Undang Nomor 35 Tahun 2014 tentang Perlindungan Anak dan Undang-Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual - Muhammad Ikhwan Adabi; Apri Rotin Djusfi; Eza Aulia; Phoenna Ath Thariq; Chandra Darusman; Jefrie Maulana (Prodi Ilmu Hukum, Universitas Teuku Umar, 2022)
This study focuses on sexual crimes in the form of obscene acts against children. According to R. Soesilo, obscene acts are all acts that violate decency or decency, or can also constitute a heinous act that is included in the environment of sexual lust. The problem lies in the criminal sanctions regulated between the two regulations. Criminal sanctions regulated in the PA Law and the PKS Law have differences in terms of the length of the sentence, the amount of the fine, and others. Then there will also be a test of the PA Law and the TPKS Law against the theory of the purpose of punishment. The research method used is a normative research method, namely research conducted with reference to the principles, legal concepts, legal norms contained in the legislation. The results of this research are that in terms of the comparison of the length of imprisonment or the number of fines, the PA Law is more effective than the TPKS Law. There are also articles regulated in the PA Law that are not regulated in the TPKS Law, such as Articles 76D and 76E. In the article, it is more specific how to commit obscene acts, namely by means of